The Role of Financial Knowledge, Income Level, Financial Behavior, and Regret Experience in Shaping Investment Decisions: A Study of Sme Business Owners With Locus of Control as A Mediator - Abidin, Gita Rosiliana; Tubastuvi, Naelati; Haryanto, Eko; Rachmawati, Erny (SENTRALISASI, 2024)
This research aims to examine investment decisions influenced by financial knowledge, income level, financial behavior, regret experience, and locus of control. This research differs from previous research, namely using the locus of control variable as a mediating variable and adding the financial behavior variable and the regret experience variable as independent variables. The investment decisions examined in this research focus on investment. As for population and sample methodology, was MSME business actors in Banjarnegara, Indonesia who already had a legal permit; using the purposive sampling method, the sampling is 180 respondents which was obtained from the Slovin formula calculation. Data analysis techniques use Structural Equation Model (SEM) PLS. The results of this study state that: first, financial knowledge and regret experience have no effect on locus of control, while income level and financial behavior have an positive effect on locus of control. second, financial knowledge, income level, financial behavior and experience of regret influence investment decisions. third, locus of control cannot mediate the influence of financial knowledge and experience of regret on investment decisions, but on the influence of income level and financial behavior on investment decisions, locus of control has a mediating role.